The second-hand effects of antibiotics: communicating the public health risks of drug resistance. Issue 3 (5th November 2019) - Langford, B J; Daneman, N; Leung, V; Wu, J H C; Brown, K; Schwartz, K L; Garber, G
Abstract: Antimicrobial resistance (AMR) poses a threat to modern medicine, but there are challenges in communicating its urgency and scope and potential solutions to this growing problem. It is recognized that AMR has a 'language problem' and the way in which healthcare professionals communicate about AMR may not always resonate with patients. Many patients are unaware that antibiotics can have detrimental effects to those beyond the recipient, due to transmission of drug-resistant organisms. The overestimation of benefits and underestimation of risks helps to fuel demand for antibiotic use in situations where they may be of little or no benefit. To better communicate risks, clinicians may borrow the term 'second-hand' from efforts to reduce smoking cessation. We present several examples where antibiotics themselves have second-hand effects beyond the individual recipient in hospitals, long-term care homes and the community. Incorporation of the concept of the second-hand effects of antibiotics into patient counselling, mass messaging and future research may help facilitate a more balanced discussion about the benefits and risks of antibiotic use in order to use these agents more appropriately.